Communication—On “Dynamic Programming for a Stochastic Markovian Process with an Application to the Mean Variance Models” by J. Goldwerger - Miller, Bruce L. (Management Science, 1978)
Communication—On “Dynamic Programming for a Stochastic Markovian Process with an Application to the Mean Variance Models” by J. Goldwerger, Management Sci. 23 (6) 612–620.